As representações sociais do professor de artes visuais no ensino médio e sua relação com a construção do conhecimento artístico do aluno - Dalla Valle, Lutiere (2008)
This research was developed in the Education Research and Arts Programme of Postgraduate Education field at the Federal University of Santa Maria/RS, with the main objective of analyzing how the Social Representations of Arts Professor in high school teaching are related to the construction of the student s artistic knowledge. The survey was developed in six high schools in the Santa Maria - three public schools and three private ones. The collected data were characterized by semi structured interviews that were analyzed in accordance with the ideas of BARDIN (1979), like content analysis. Intending to discuss and analyzing the present conflicts in the relation teaching/learning, the research was conducted through qualitative approach, with exploratory character, using the Social Representations Theory proposed by MOSCOVICI, (1978 and 2003) and complemented by authors such as JODELET, (1984 and 2001); GUARESCHI & JOVCHELOVITCH, (1995); WOOD, ( 2000); SÁ, (1998); SPINK, (1995), among others, and in the fields of art and education, subsidized by theorists who work with different approaches regarding the construction of knowledge in visual arts, such as BARBOSA, (1998, 2002 and 2005); HERNÁNDEZ, (1998, 2000, 2005 and 2007); PILLAR, (2001); SANCHO, (2006), among other authors. Thus, through the reports of the interviews we found that the representations attributed to a Visual Arts professor, by himself/herself and by his/her students, present some differences and convey stereotyped aspects in their constitution. The Social Representations and their ability to influence the relations of learning have become evident by the teaching action contextualization ruled by criteria and social models, valorative issues and powers of acquisition.